Practical Procedures in Ensuring Quality Primary Education in Nigeria - Adekunle Thomas Olutola; Nuraddeen Yusuf Galadanchi; Rafiu Ademola Olatoye; Kelechi Joshua Princewill Ihechu (Universitas Pendidikan Indonesia (UPI), 2022)
Universally, education is considered to be a basic parameter that determines the change and transformation in the socio-political, scientific, and technological spheres of every nation. The primary phase of education, though not given the deserved attention in Nigeria foundation of the entire educational system. A functional, qualitative, and comprehensive primary education curriculum is needed to drive the national development agenda. This paper advocated that the qualitative primary school is what can make education at higher levels an important instrument for national development. Some challenges such as poor funding, incompetent teachers, inadequate supervision/inspection as well as non-regular assessment among others were identified as problems militating against primary education in Nigeria. However, some suggestions were made such as; the introduction of entrepreneurship education in schools and the conduct of regular supervision and inspection should be made. Above all, the budget for education especially primary schools should be improved.